THE EFFECTIVENESS OF PROJECT-BASED BIOTECHNOLOGY E-LKPD ON LEARNING OUTCOMES AT SMAN 3 SIAK HULU, KAMPAR REGENCY, RIAU - Siska Firanda; Ibnu Hajar (SOSIOEDUKASI, 2026)
This research is motivated by the low learning outcomes of students in biotechnology materials caused by the use of teaching materials that have not been able to encourage active involvement of students in the learning process. One of the alternatives that can be used to overcome these problems is the implementation of project-based biotechnology Electronic Worksheets (E-LKPD). This study aims to determine the effectiveness of project-based biotechnology E-LKPD on the learning outcomes of class X students at SMAN 3 Siak Hulu, Kampar Regency, Riau. The research uses a quantitative approach with a quasi experiment method through a Nonequivalent Control Group Design. The research sample consisted of two classes, namely the experimental class and the control class which each amounted to 39 students and was selected using a simple random sampling technique. The research instrument is in the form of learning outcome tests that have met the validity and reliability tests. Data analysis was carried out descriptively and inferentially through normality tests, homogeneity tests, Independent Samples t-Test, and effect size analysis (Cohen's d) using IBM SPSS Statistics 26. The results showed that there was a significant difference in learning outcomes between the experimental class and the control class with a value of Sig. (2-tailed) = 0.001 (p < 0.05). The effect size value (Cohen's d) of 0.813 shows that the use of project-based biotechnology E-LKPD has a great influence on improving student learning outcomes. Thus, it can be concluded that project-based biotechnology E-LKPD is effective in improving student learning outcomes in biotechnology materials at SMAN 3 Siak Hulu, Kampar Regency, Riau.